2004
DOI: 10.1111/j.1365-2710.2003.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical pharmacist interventions on drug interactions in outpatient pharmaceutical HIV-care

Abstract: Objective: To evaluate the usefulness of intervention in drug interactions of antiretroviral drugs with coadministered agents by a clinical pharmacist in outpatient HIV-treatment. Methods: The study design included two intervention arms (A and B), which were both preceded by a control observation period. In arm A, a complete list of the currently used drugs, extracted from pharmacy records was provided to the treating physician. In arm B the same list was provided but with a notification when a drug interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 21 publications
2
43
0
2
Order By: Relevance
“…Clinically significant drug interactions in HIV patients 277 knowledge and collaborating with the physician, thus optimizing drug treatments in HIV-infected patients. Several studies have shown that treatment reviews by pharmacists integrated in multidisciplinary teams can reduce the number of prescription drugs and reduce the rate of mortality and morbidity associated with iatrogenic diseases caused by drug use [4,25,26]. The authors consider it necessary to select only those alerts that identify important interactions in clinical practice, as an excess of information may lead to saturation at the time of clinical decision making [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically significant drug interactions in HIV patients 277 knowledge and collaborating with the physician, thus optimizing drug treatments in HIV-infected patients. Several studies have shown that treatment reviews by pharmacists integrated in multidisciplinary teams can reduce the number of prescription drugs and reduce the rate of mortality and morbidity associated with iatrogenic diseases caused by drug use [4,25,26]. The authors consider it necessary to select only those alerts that identify important interactions in clinical practice, as an excess of information may lead to saturation at the time of clinical decision making [27].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically significant drug interactions (CSDIs) involving antiretroviral agents have been reported in 30-41.2% of HIV-positive patients in the USA [3], and 20-23% in the Netherlands [4]. Several studies have suggested a positive correlation between increased age and increased risk for drug interactions in HIV-positive patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] This is the first study we are aware of that demonstrates a reduction in the duration of HAART errors in a hospital as a result of a clinical pharmacist's interventions.…”
Section: Medication-disease Interaction (Renal Insufficiency)mentioning
confidence: 93%
“…It therefore follows that significant changes in HCV therapy could profoundly improve the treatment outcomes of this patient group. However, the addition of combination therapies, which include novel agents, for patients who are taking ARV regimens is unlikely to be without complication; clinically significant DDIs involving ARVs are common, affecting 27% of 159 HIV-infected outpatients in a UK study [9] and 23-26% of 220 HIVinfected outpatients in a study in The Netherlands [10].…”
Section: Recent Findingsmentioning
confidence: 99%